A Review on Recent Advances of Natural Products as Larvicides in Vector Control Management - Rahaman, Muktarul; Gope, Arpita; Khanrah, Jayeeta; Rawani, Anjali (Jordan Journal of Pharmaceutical Sciences, 2024)
The mosquito, a biological vector, is responsible for the transmission of serious and dreaded diseases worldwide. These diseases, which are chiefly endemic to tropical countries, cause millions of deaths each year. The significance of plant-based and environmentally friendly insecticides has increased in recent years. Due to their easy biodegradability and target selectivity, they can be used safely in aquatic environments. Despite their effectiveness in controlling target vector species, pesticide applications pose a threat as they can lead to increased chemical insecticide resistance, causing a rebound in vectorial capacity. This review explores the efficacy of phytochemicals in controlling mosquito populations. In mosquito control programs, phytochemicals play a significant role. Plants serve as an immense repository for primary and secondary metabolites. Various types of polar and nonpolar solvents can be used to extract the bioactive plant ingredient(s) from either the whole plant or a specific part of it. This literature review defines natural products and provides an overview of the different types of natural products that can be used to control mosquito larvae. Particularly, it examines the effectiveness of natural products in vector control without causing resistance or harm to non-target organisms. The purpose of this paper is to offer a comprehensive review of the use of natural products as mosquito larvicides and to underscore their potential as an alternative to traditional chemical methods. Ultimately, it encourages further research into the development and use of natural products for successful vector mosquito control.